IMPACT OF ACTIVITY-BASED TEACHING ON IMPROVING LEARNING: AN EMPIRICAL EXPLORATION IN SCIENCE SUBJECTS - Rakhshanda Rashid; Dr. Muhammad Tahir Nadeem; Nosheen Malik (International Journal of Contemporary Issues in Social Sciences, 2024)
This study explored the effectiveness of activity-based teaching (ABT) to improve learning among grade 8 science students. Experimental research Single subject design ABA was selected to conduct the study. The population was all public schools in District Lodhran. Thirty-five grade 8 students from the current academic year (2023-24), were selected as the subject of the study seven general science concepts were designed for grade 8 students. In the initial phase, the curriculum content was outlined and a table of specifications was developed. Before the treatment, students' initial learning level was assessed through a pretest. To ensure validity, the study design gets reviewed by secondary school teachers, educators and educational experts. After sixteen weeks of treatment of ABT approach, post-tests were administered. The results of the study depicted that the activity-based intervention significantly impacted the students' learning. The study revealed that implementing activity-based teaching; significantly rally the student’s skill to transform knowledge into solution of various daily situations.